Reconstructing The Meaning of Education: An Exploration of The Homeschooling Experience among Families in Yogyakarta, Indonesia - Listiarini, Sri; Abdullah, Irwan (Universitas Muhammadiyah Surakarta, 2023)
This paper presents the phenomenon of homeschooling in Yogyakarta, a city known as one of the centers of education in Indonesia, through a social construction perspective. Previous studies on homeschooling in Indonesia have mostly focused on the pedagogical perspective. This research aims to outline the process that homeschooler families go through in choosing to homeschool instead of sending their children to school. The qualitative method used is in-depth interviews with parents who have been practicing homeschooling in their families for years. The findings in this study show that the informants have experienced the reconstruction of the meaning of education from school to homeschooling through three stages: first, the informants get various information about homeschooling from various sources but mainly from previous homeschooling practitioners and pioneers; second, the concept of homeschooling is crystallized by the informants into their thinking; third, the informants implement the concept of homeschooling by educating their children at home rather than sending them to school. Parenting-related materials play an important role in fostering parents' initial interest in homeschooling. The development of information technology made it easier for informants to access various information related to homeschooling.